The gut-brain axis in the pathogenesis of Parkinson's disease. Issue 2 (June 2019) - Meng, Lanxia; Yuan, Xin; Cao, Xuebing; Zhang, Zhentao
Parkinson's disease (PD) is the second most common neurodegenerative disease. Its pathological markers include Lewy bodies and Lewy neuritis, which primarily affect the substantia nigra. However, in recent years, mounting evidence suggests that PD is a multifocal neurodegenerative process that influences several neuronal structures aside from the substantia nigra, one of which is the enteric nervous system. Many clinical studies have reported that patients with PD experience gastrointestinal dysfunction for many years before the onset of motor symptoms. Emerging evidence indicates that α-synuclein deposition may start in the enteric nervous system and then propagate to the central nervous system. The gut-brain axis plays an important role in PD pathogenesis. Recent evidence suggests that these interactions may be primarily affected by the intestinal microbiota. In this review, the authors discuss recent research, and illustrate how changes in the composition of the gut microbiota may trigger inflammation, thus contributing to neurodegeneration in PD.